Adipocytes Under Obese-Like Conditions Change Cell Cycle Distribution and Phosphorylation Profiles of Breast Cancer Cells: The Adipokine Receptor CAP1 Matters - Bergqvist, Malin; Elebro, Karin; Borgquist, Signe; Rosendahl, Ann H. (Frontiers in Oncology, 2021)
Background: Obesity and associated metabolic conditions impact adipocyte functionality with potential consequences for breast cancer risk and prognosis, but contributing mechanisms remain to be understood. The adipokine receptor adenylyl cyclase-associated protein-1 (CAP1) has been implicated in the progression of breast cancer, but results are conflicting and the underlying molecular mechanisms are still unknown. In this study, molecular and cellular effects in breast cancer cells by stimulation of adipocytes under normal or obese-like conditions, and potential involvement of CAP1, were assessed. Material and methods: Estrogen receptor (ER)-positive T47D and ER-negative MDA-MB-231 breast cancer cells were exposed to adipocyte-secretome from adipocytes placed under pressures mimicking normal and obese-like metabolic conditions. Changes in phosphorylated kinase proteins and related biological pathways were assessed by phospho-antibody array and PANTHER analysis, cell proliferation were investigated through sulforhodamine B, cell cycle distribution by flow cytometry. Functional effects of CAP1 were subsequently examined following small interfering (si)RNA-mediated knockdown. Results: Protein phosphorylations involved in important biological processes were enriched in T47D breast cancer cells in response to adipocyte secretome from obese-like compared with normal conditions. The obesity-associated adipocyte secretome further stimulated cell proliferation and a shift from cell cycle G1-phase to S- and G2/M-phase was observed. Silencing of CAP1 decreased cell proliferation in both T47D and MDA-MB-231 cells, and reduced the obesity-associated secretome-induction of phosphoproteins involved in cell proliferation pathways. Conclusions: These results indicate that the adipocyte secretome and CAP1 are mechanistically important for the proliferation of both ER-positive and ER-negative breast cancer cells, and potential signaling mediators were identified. These studies provide biological insight into how obesity-associated factors could affect breast cancer.